Nitretação de aço inoxidável duplex UNS S32750 por plasma de radiofrequência indutivamente acoplado - Souza, André Augusto Bonfante de (2020)
Nitriding is a thermochemical treatment based on nitrogen diffusion in ferrous alloys to improve its mechanical performance, such as wear resistance and fatigue, and also its corrosion behavior. Stainless steels are generally low-temperature nitrided. The duplex grade of stainless steels is, however, poorly investigated, especially when treated by radiofrequency (RF) plasmas. In the present work the radio-frequency inductively coupled plasma (ICP) nitriding of UNS S32750 duplex stainless steel with and without DC bias was evaluated, regarding layer thickness, microhardness and composition of the developed microstructure. Treatments were carried out for 4 hours at 400 and 450 ºC. They presented expanded layers up to 11,6 µm with variations between phases and maximum nitrogen content of 13%wt. Average microhardness were increased from 347 HK0,050 (non-treated material, both phases) to 990/765 and 2367/1209 on ferritic and austenitic phases, at 400 and 450 ºC, respectively. XRD-detected phases on the layers are expanded austenite (for 400 and 450 ºC) and chromium nitrides at 450 ºC. The study showed the efficiency of RF-ICP nitriding of duplex stainless steels and diagnosed the DC bias voltage as a key parameter of layer growth.